A performance analysis of government or state-backed unit trusts in Malaysia / Masridawati Musa - Musa, Masridawati (1997)
A unit trust combines the capital of many investors, usually small investors, to employ professional management to purchase securities of many companies thus providing diversification and supervision which the small investors could not individually afford to do.